Profile of Student Mathematical Reasoning Ability in Making Proof - Maimunah, Maimunah; Kartini, Kartini (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The purpose of this study is to describe how the students mathematical reasoning profiles in making proof in the real analysis course. This research is a descriptive research. Techniques used to collect data is to provide tests to 25 students of semester V in Real Analysis courses. Data analysis is done by reducing data, presenting data, and make conclusions. The results showed that the students ability in making proof includes four mathematical reasoning indicators: making guesses, doing mathematical manipulations, giving reasons/explanations, and drawing conclusions. The four mathematical reasoning indicators appear in high-ability students, while midle- ability students are mastering two to three indicators of mathematical reasoning, and low-ability students master one mathematical reasoning indicator.